The Influence of Financial Literacy as a Mediation of the Relationship Between Behavioral Bias and Decisions in Investing Employees in Jabodetabek - Hotniko Hildebrandus; Hamdy Hady; Febria Nalurita (International Journal Labs, 2023)
This study aims to determine how Behavior Biases influences people in making investment decisions. The Independent Variable used in this study is Behavior Biases consist of Overconfidence, Herding, Risk-aversion and Disposition. Dependent Variable used in this study is Investment Decision. The moderating variable used in this study is Financial Literacy. This study taking samples from workers lives in Jabodetabek (Jakarta, Bogor, Depok and Bekasi), Indonesia. By using data collection method via Google Forms spreaded to public of Jabodetabek 2022-2023 thus obtaining 353 respondents who became the research sample. The data analysis used to test the hypothesis is the analysis of the regression equation using SEM PLS (Structural Equation Model Partial Least Square) program. The result of this study indicates that Bias Behavior (Overconfidence, Herding, Risk Aversion, Disposition) has an influence on Investment Decisions, while Financial Literacy has no effect and Financial Literacy doesn't moderate Bias Behavior towards Investment Decisions. This finding has implications for potential investors to consider learning Financial Literacy more in their investment decisions.